The future of critical interdisciplinary accounting research: Performative ontology and critical interventionist research - Lukka Kari; Becker Albrecht (Elsevier (Commercial Publisher), 2025)
The matter of care in this thought piece is the future of the critical interdisciplinary accounting research (IPA) project. On the one hand, the need for critical IPA research is arguably increasing today, not least due to the very serious, complex and ‘wicked’ global problems – like climate change, decreasing biodiversity, over-population, global inequality and COVID-19. On the other hand, however, critical IPA research faces some severe challenges, such as the dominance of mono-disciplinary normal science, limitations of getting access to organisations, and a certain academic insularity. To discuss possibilities for furthering critical IPA research, we start from approaches to critical performativity and suggest to complement them with ideas from two very different research approaches. First, we suggest that the concept of performative ontology and the related diverse economies approach, introduced by Gibson-Graham (2008), goes a step further than previous conceptualizations of critical performativity in methodological as well as practical terms. Secondly, we argue that employing some of the inherent ideas and learning points of interventionist research in conjunction with performative ontology can inspire new ways of conducting critical IPA research that matters.